Effects of Pretreatment and Drying on the Volatile Compounds of Sliced Solar-Dried Ginger (Zingiber officinale Roscoe) Rhizome. (8th January 2022) - Amoah, Roseline Esi; Wireko-Manu, Faustina Dufie; Oduro, Ibok; Saalia, Firibu Kwesi; Ellis, William Otoo; Dodoo, Alexander; Dermont, Charles; Manful, Maame Ekua
Abstract : Ginger ( Zingiber officinale Roscoe) rhizomes are mostly used as spice and medicine due to their high aroma intensity and medicinal bioactive compounds. However, the volatile compounds of ginger, partly responsible for its aroma and medicinal properties, can be affected by the pretreatment, drying method, and extraction processes employed. The objective of this study was to assess the effects of pretreatment and drying on the volatile compounds of yellow ginger variety at nine months of maturation. The effect of potassium metabisulfite (KMBS) and blanching pretreatment and drying on the volatile compounds of ginger using head space solid-phase microextraction with GCMS/MS identification (HS-SPME/GCMS/MS) was investigated. KMBS of concentrations 0.0 (control), 0.1, 0.15, 0.2, and 1.0% and blanching at 50°C and 100°C were used for pretreatment and dried in a tent-like concrete solar (CSD) dryer and open-sun drying (OSD). The different concentrations of KMBS-treated fresh ginger rhizomes did not result in any particular pattern for volatile compound composition identification. However, the top five compounds were mostly sesquiterpenes. The 0.15% KMBS-treated CSD emerged as the best pretreatment for retaining α -zingiberene, β -cubebene, α -farnesene, and geranial. The presence of β -cedrene, β -carene, and dihydro- α -curcumene makes this study unique. The 0.15% KMBS pretreatment and CSD drying can be adopted as an affordable alternative to preserve ginger.